Asuhan Keperawatan Gangguan Pola Tidur pada Pasien GGK yang Menjalani Hemodialisa dengan Terapi Relaksasi Nafas dalam Combain Inhalasi Aromatherapy Lavender di Ruang Rawat Inap : (RSUP Dr. Kariadi Semarang) - Siti Al Maroh; M Jamaluddin (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Chronic Kidney Failure (CKD) is a condition of permanent and progressive decline in kidney function. CKD patients undergoing hemodialysis often experience sleep disturbances, which impact their physical and psychological condition. Non-pharmacological interventions such as deep breathing relaxation and lavender aromatherapy can be alternative therapies to address these disorders. This study analyzes nursing care for sleep disturbances in CKD patients undergoing hemodialysis and evaluates the effectiveness of deep breathing relaxation therapy combined with lavender aromatherapy inhalation. This study used a case study approach with three CKD patients undergoing hemodialysis and experiencing sleep disturbances. The intervention was carried out for three days with a combination of deep breathing relaxation therapy and lavender aromatherapy inhalation. After three days of intervention, complaints of insomnia decreased in all three patients. The sleep pattern score increased to 5, indicating undisturbed sleep patterns. Deep breathing relaxation therapy combined with lavender aromatherapy inhalation is effective in addressing sleep disturbances in CKD patients undergoing hemodialysis. This therapy is recommended as an additional intervention in the hospital and should be carried out with family support to increase patient comfort.